Perjanjian Perkawinan pada Masyarakat Suku Dayak Ngaju Ditinjau dari Hukum Positif: Marriage Agreements in the Dayak Ngaju Community from the Perspective of Positive Law - Khair, Abdul; Adawiyah, Rabiatul (Anterior Jurnal, 2024)
This research is motivated by the existence of marriage agreements among the Dayak Ngaju community, which are made before the marriage and stipulate that if one of the spouses violates the marriage, such as through infidelity or by attempting to unilaterally dissolve the marriage, they will be subjected to 'jipen/singer' by the customary leader, which involves the payment of a fine agreed upon at the time the marriage agreement was made. The method used in this research is qualitative descriptive, with data collection through interviews, observation, and documentation. The findings of this research show that marriage agreements among the Dayak Ngaju people serve to provide legal protection for women and their children concerning property matters during the marriage. Additionally, the marriage agreement also functions as a guarantee of fidelity between spouses, ensuring that the marriage cannot be easily dissolved without clear reasons and by the law.